Three‐dimensional computed tomography of portopulmonary venous anastomoses in patients with esophageal varices before treatment. Issue 6 (8th October 2015) - Matsumoto, Yasuhiro; Hidaka, Hisashi; Matsunaga, Keiji; Kubota, Kousuke; Yamane, Keiko; Inoue, Tomoyoshi; Minamino, Tsutomu; Takada, Juichi; Tanaka, Yoshiaki; Okuwaki, Yusuke; Nakazawa, Takahide; Shibuya, Akitaka; et al.
Abstract : Aim: Portopulmonary venous anastomoses (PPVA) are shunts between esophageal varices and pulmonary veins. Because PPVA can cause serious complications at the time of sclerotherapy for esophageal varices, it is essential to confirm the existence of any PPVA before treatment. Methods: The study group comprised 101 patients in whom hemodynamics were evaluated on three‐dimensional computed tomography (3D‐CT) before either elective or prophylactic treatment of esophageal varices at Kitasato University East Hospital from October 2007 through August 2013. The presence or absence of PPVA, laboratory test results and 3D‐CT findings were retrospectively examined in these patients. Results: Nine patients had PPVA, and 92 patients did not. The underlying diseases in the PPVA group were: hepatitis C liver cirrhosis in three; non‐B, non‐C liver cirrhosis in three; non‐alcoholic steatohepatitis in one; primary biliary cirrhosis in one; and autoimmune hepatitis in one. The distribution of underlying diseases did not differ between the PPVA group and the non‐PPVA group. When the study variables were statistically compared between the groups, the incidence of large, coil‐shaped esophageal varices (grade F3) differed significantly between the groups ( P = 0.001). Multivariate analyses of factors related to PPVA revealed that only the grade F3 type of esophageal varices differed significantly between the groups ( P = 0.005; hazard ratio, 5.21; 95% confidence interval, 3.1–16.4). Conclusion: In patients with grade F3 esophageal varices, the treatment method should be selected on the basis of an accurate hemodynamic analysis using 3D‐CT before therapy.